20:4-NAPE induced changes of mechanical sensitivity and DRG neurons excitability are concentration dependent and mediated via NAPE-PLD - Bhattacharyya, Anirban; Vasconcelos, Daniel; Spicarova, Diana; Palecek, Jiri (Scientific reports, 2025)
Alterations in the excitability of dorsal root ganglion (DRG) neurons are critical in the pathogenesis of acute and chronic pain. Neurotransmitter release from the terminals of DRG neurons is regulated by cannabinoid receptor 1 (CB1) and transient receptor potential vanilloid 1 (TRPV1), both activated by anandamide (AEA). In our experiments, the AEA precursor N-arachidonoylphosphatidylethanolamine (20:4-NAPE) was used to study the modulation of nociceptive DRG neurons excitability using K+-evoked Ca2+ transients. Intrathecal administration was used to evaluate in vivo effects. Application of 20:4-NAPE at lower concentrations (10 nM - 1 µM) decreased the excitability of DRG neurons, whereas the higher (10 µM) increased it. Both effects of 20:4-NAPE were blocked by the N-acylphosphatidylethanolamine phospholipase D (NAPE-PLD) inhibitor LEI-401. Similarly, lower concentrations of externally applied AEA (1 nM - 10 nM) inhibited DRG neurons, whereas higher concentration (100 nM) did not change it. High AEA concentration (10 µM) evoked Ca2+ transients dependent on TRPV1 activation in separate experiments. Inhibition of the CB1 receptor by PF514273 (400 nM) prevented the 20:4-NAPE- and AEA-induced inhibition, whereas TRPV1 inhibition by SB366791 (1 µM) prevented the increased DRG neuron excitability. In behavioral tests, lower 20:4-NAPE concentration caused hyposensitivity, while higher evoked mechanical allodynia. Intrathecal LEI-401 prevented both in vivo effects of 20:4-NAPE. These results highlight anti- and pro-nociceptive effects of 20:4-NAPE mediated by CB1 and TRPV1 in concentration-dependent manner. Our study underscores the complexity of endocannabinoid signaling in pain transmission modulation and highlights 20:4-NAPE as a potential therapeutic target, offering new insights for developing analgesic strategies.
Keywords: Phospholipase D; Male; polynenasycené alkamidy; Polyunsaturated Alkamides; Calcium; neurony; NAPE-PLD; endokanabinoidy; Animals; Neurons; CB1; Receptor, Cannabinoid, CB1; TRPV Cation Channels; mužské pohlaví; krysa rodu Rattus; Ganglia, Spinal; Rats; Rats, Sprague-Dawley; Endocannabinoids; vápník; fosfolipasa D; DRG neurons; Anandamide; zvířata; potkani Sprague-Dawley; kyseliny arachidonové; Arachidonic Acids; receptor kanabinoidní CB1; TRPV1; kationtové kanály TRPV; spinální ganglia; fosfatidylethanolaminy; 20:4-NAPE; Phosphatidylethanolamines